Antioxidant and protective effects of Royal jelly on histopathological changes in testis of diabetic rats - Ghanbari, Elham (Int J Reprod Biomed, 2016)
BACKGROUND: Diabetes is the most common endocrine disease. It has adverse effects on male reproductive function. Royal Jelly (RJ) has antioxidant and anti-diabetic effects and show protective effects against diabetes. OBJECTIVE: This study was conducted to evaluate the effect of RJ on histopathological alterations of the testicular tissue in streptozotocin (STZ)-induced diabetic rats. MATERIALS AND METHODS: In this experimental study, 28 adult Wistar rats were randomly divided into control (C), royal jelly (R), diabetic (D) and RJ-treated diabetic (D+R) groups. Diabetes was induced by a single intraperitoneal injection of STZ at 50 mg/kg body weight (BW). The rats from the R and D+R groups received daily RJ (100 mg/kg BW) for 6 wks orally. Hematoxylin-Eosin staining was used to analyze histopathological changes including: tunica albuginea thickness (TAT), seminiferous tubules diameter (STsD), Johnsen’s score, tubular differentiation index (TDI), spermiogenesis index (SPI), Sertoli cell index (SCI), meiotic index (MI), and mononuclear immune cells (MICs) in testes. The antioxidant status was examined by evaluating testicular levels of ferric reducing antioxidant power (FRAP) and catalase (CAT) activity. RESULTS: Histological results of the testis from diabetic rats showed significant decrease in STsD, Johnsen’s score, TDI, SPI, SCI and MI, and significant increase in TAT and MICs, while administration of RJ significantly reverted these changes (p<0.05). RJ treatment markedly increased activity of CAT and FRAP. There were significant differences in FRAP levels among C (13.0±0.5), RJ (13.4±0.3), D (7.8±0.6) and D+R (12.4±0.7) groups (p<0.05). CONCLUSION: RJ improved diabetes-induced impairment in testis, probably through its antioxidant property.